2012
DOI: 10.1021/nl301804c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects from Graphene and Carbon Nanotubes Enable Flexible and Robust Electrodes for High-Performance Supercapacitors

Abstract: Flexible and lightweight energy storage systems have received tremendous interest recently due to their potential applications in wearable electronics, roll-up displays, and other devices. To manufacture such systems, flexible electrodes with desired mechanical and electrochemical properties are critical. Herein we present a novel method to fabricate conductive, highly flexible, and robust film supercapacitor electrodes based on graphene/MnO(2)/CNTs nanocomposites. The synergistic effects from graphene, CNTs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
411
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(429 citation statements)
references
References 36 publications
16
411
2
Order By: Relevance
“…The structural rigidity of VGNS can prevent the restacking of graphene nanosheets, a commonly observed problem in horizontal graphene. [20][21][22] Using a simple solvothermal method, we further show that MoS 2 nano-leaves with a thickness of~3 nm can be directly grown on VGNS with a controllable mass loading and pore size distribution. This unique nanoarchitecture design offers several attributes for effective energy storage and conversion.…”
Section: Introductionmentioning
confidence: 89%
“…The structural rigidity of VGNS can prevent the restacking of graphene nanosheets, a commonly observed problem in horizontal graphene. [20][21][22] Using a simple solvothermal method, we further show that MoS 2 nano-leaves with a thickness of~3 nm can be directly grown on VGNS with a controllable mass loading and pore size distribution. This unique nanoarchitecture design offers several attributes for effective energy storage and conversion.…”
Section: Introductionmentioning
confidence: 89%
“…Such structures may find their applications in biomedical engineering like expanding blood vessels radically without exerting any axial stretch. One of the important feature of C-honeycomb is its ultra-light weight with tunable cell sizes that may be employed as electrodes for batteries with ultrafast charge and discharge rates 37 , flexible supercapacitor electrodes 38 , and storage media 39 . The density 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 15 of C-honeycombs with ܽ = 5.8Å to 29.7Å are only 1.31 g/cm 3 to 0.31 g/cm 3 , much lower than 3.52 g/cm 3 for diamond and 2.26 g/cm 3 for graphite 40 .The high specific strength of 3-D C-honeycomb render it extremely competitive for the use as an ultra-light weight architected functional material 41 .…”
mentioning
confidence: 99%
“…In addition, PEDOT/PSS can act as an e®ective dispersant and binder for improving the adhesion to the substrate and the connection among MnO 2 / CNTs particles. Similarly, Cheng and co-workers 135 (2012) adopted novel approach of fabricating ternary nanocomposites of graphene-MnO 2 -CNTs via direct growth of MnO 2 nanoparticles and CNTs on graphene substrate. CNTs which provide electronic conductivity and mechanical reinforcement in combination with highly electrochemically active MnO 2 nanoparticles and high-surface-area graphene enable the synergetic e®ects for superior nanocomposite electrodes.…”
Section: Ternary Compositesmentioning
confidence: 99%
“…These°exible electrodes successfully deliver high speci¯c capacitance of 372 F/g without the need of current collectors and binders. 135 Another research group has reported on a novel PANI/TiO 2 /graphene oxide (GO) composite which demonstrated the highest speci¯c capacitance of 1020 F/g. 111 TiO 2 nanoparticles serve as avenue for electrode to penetrate to three-dimensional graphene oxide-PANI networks, facilitating the Faradaic reactions of PANI.…”
Section: Ternary Compositesmentioning
confidence: 99%